Identifying Factors Associated With Variation in Telemental Health Delivery at Federally Qualified Health Centers - Brianna Lombardi; Connor Sullivan; Maria Gaiser; Lisa de Saxe Zerden; Evan Galloway; Brad Wright (SAGE Publishing, 2024)
Background: COVID-19 accelerated federally qualified health centers' use of telemental health. However, factors associated with telemental health service delivery remain unclear. We examined telemental health delivery by clinician type and mental health workforce composition across the U.S. to understand how staffing and other organizational characteristics are related to telemental health delivery at health centers. Methods: Using data from the 2021 Uniform Data System, we characterized the proportion of mental health care delivered via elemental (i.e., virtual visits) at health centers in the U.S. that received HRSA grant funding (n = 1,270) overall and by state and clinician type. Then, we conducted multivariate beta regression analyses to assess the proportion of mental health visits delivered via telemental health at health centers as a function of mental health workforce composition, while adjusting for health center size, patient mix, and state. Results: In 2021, health centers delivered 43% of their mental health visits via telemental health, with significant variation by state and clinician type. On average, the proportion of mental health visits delivered via telemental health was greater among psychiatrists (61%, P  < .001) than psychologists (49%) and clinical social workers (45%). Factors significantly associated with the increased proportion of telemental health delivered by health centers included a higher supply of psychiatrists per patient, more grant dollars per patient, and a greater proportion of Asian patients served. Conclusions: Access to telemental health varies by state and across health centers based on mental health workforce composition. Future work is needed to examine funding and workforce strategies to increase telemental health service availability.